2019
DOI: 10.1111/bjep.12291
|View full text |Cite
|
Sign up to set email alerts
|

Self‐affirmation reduces the socioeconomic attainment gap in schools in England

Abstract: Background. Studies in the United States show that school students from some ethnic backgrounds are susceptible to stereotype threat, that this undermines their academic performance, and that a series of virtually zero-cost self-affirmation writing exercises can reduce these adverse effects. In England, however, socioeconomic status (SES) is a much stronger predictor of academic success than is ethnic background.Aims. This study investigates whether self-affirmation writing exercises can help close the SES att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 76 publications
2
24
0
Order By: Relevance
“…It was expected based upon the wider literature and a previous study conducted by the authors on the same dataset [ 62 ], that IQ and socio-economic status would predict maths attainment trajectories across the transition from primary to secondary education. Research investigating IQ and SES and attainment has found similar results [ 110 112 ], with this study adding further support to the existing literature.…”
Section: Discussionsupporting
confidence: 86%
“…It was expected based upon the wider literature and a previous study conducted by the authors on the same dataset [ 62 ], that IQ and socio-economic status would predict maths attainment trajectories across the transition from primary to secondary education. Research investigating IQ and SES and attainment has found similar results [ 110 112 ], with this study adding further support to the existing literature.…”
Section: Discussionsupporting
confidence: 86%
“…This finding is not surprising as research has consistently found links between SES and both general academic achievement (for a review see [72]), and maths performance specifically (e.g. [105]). Although, this study provides additional evidence that children with higher SES progress at a very slightly quicker rate compared with their peers.…”
Section: Contextual Predictors Of Maths Attainmentmentioning
confidence: 78%
“…Yet, values affirmation interventions have been found to benefit other groups in different contexts. In England, with its long history of striking disparities between social classes (Evans, 2006; O. Jones, 2016), a brief values affirmation intervention has been shown to increase the mathematics exam performance of students from low SES backgrounds, reducing the gap with their higher SES peers by a remarkable 62% (covariate adjusted; Hadden, Easterbrook, Nieuwenhuis, Fox, & Dolan, 2019). However, in contrast with the U.S. studies, it found no evidence of benefits to lower performing ethnic groups.…”
Section: Wise Interventionsmentioning
confidence: 99%
“…These psychological barriers are often the consequences of cues within local educational contexts that signal to some groups-usually those with low status that have suffered from inequality in wider society-that they are not valued in educational institutions, are likely to fail at their studies, and are unlikely to reap any benefits from pursuing an education. This can cause members of those groups to feel alienated, uncomfortable, discouraged, and demotivated, impeding their engagement, persistence, progress, and performance within education (Easterbrook, Hadden, & Nieuwenhuis, 2019). These psychological barriers can therefore account for a substantial proportion of the differences in educational attainment between groups (Walton & Yeager, 2020).…”
mentioning
confidence: 99%